Exploring hematopoietic stem cell awareness and engagement among healthcare professionals: A cross-sectional survey - Vikash Chandra Mishra; Dinesh Chandra; Anoushka Raina; Vimarsh Raina (Indian Journal of Community and Family Medicine)
Introduction: Hematopoietic stem cell transplantation (HSCT) is a crucial treatment for various blood disorders. However, the scarcity of matched related donors has led to the establishment of stem cell donor databases, commonly known as stem cell registries. These registries aim to streamline the identification of unrelated volunteer stem cell donors for matched unrelated donor HSCT. This study specifically aims to assess the level of knowledge and engagement among healthcare professionals in Delhi National Capital Region (NCR) regarding hematopoietic stem cell (HSC) donation. Material and Methods: The cross-sectional observational study involved 240 healthcare professionals was conducted in the Delhi. Results: The study findings indicate that the level of awareness about HSC and transplants among healthcare professionals was 44.25 and 40%, respectively, revealing a substantial knowledge gap in this field. Surprisingly, none of the participants reported prior experience with stem cell donation. However, a noteworthy 70.4% expressed a willingness to be part of the stem cell registry. Conclusion: The study emphasizes the urgent need for comprehensive education and awareness initiatives, especially targeting healthcare professionals, to bridge the knowledge gap and boost volunteer stem cell donor registrations for the benefit of patients requiring HSCT. The results serve as a foundation for fostering a more informed and engaged community in the field of HSCs, underscoring the importance of proactive measures to enhance knowledge and participation.